POPULAR AND ERUDITE IN SCHOOL EDUCATION - Cláudio Félix dos Santos; Adalgiza Gonçalves Gobbi; Ana Carolina Galvão Marsiglia (Germinal : Marxismo e Educação em Debate, 2015)
This article aims at analyzing and questioning the relationship between erudite and popular knowledge as a challenge to developing a historical-critical educational study. Starting from a brief report about the history of composers Luiz Gonzaga and Humberto Teixeira, we walked a theoretical path, exploring the formulation of historical-critical pedagogy about the need of producing ways for individuals to have access to systematized knowledge so as to express their interests in an elaborate way.